EMPLOYEE RETENTION STRATEGY IN MSMES IN KENDARI CITY; REDUCING TURNOVER THROUGH IMPROVED WELL-BEING AND CAREER DEVELOPMENT - Dwianto, Ikhsan; Mokodompit, Eliyanti Agus (Penelitian dan Pengembangan Ilmu, 2024)
Employee retention is a complex challenge for SMEs in Indonesia, given the high turnover rates that can disrupt company stability and productivity. In the context of SMEs in Kendari, this issue has become more urgent due to the lack of effective human resource policies to retain quality employees. This study identifies a knowledge gap regarding effective retention strategies in SMEs, focusing on employee welfare and career development. The research employs a qualitative approach, conducting in-depth interviews with SME owners, employees, and HR practitioners to gather data on the factors influencing employee retention. The findings provide practical implications for designing better HR management policies in SMEs, which can reduce turnover rates and enhance employee loyalty and productivity. Additionally, this study contributes theoretically to the development of knowledge on human resource management in small businesses, which are often overlooked in managerial literature.